Body Mapping and Story Circles in Sexual Health Research With Youth of Color: Methodological Insights and Study Findings From Adolescent X, an Art-Based Research Project. Issue 4 (July 2022) - Brodyn, Adriana; Lee, Soo Young; Futrell, Elizabeth; Bennett, Ireashia; Bouris, Alida; Jagoda, Patrick; Gilliam, Melissa
We describe the implementation and select findings from Adolescent X, an arts-based research project that used story circles and body mapping to elucidate how young people understand the relationship between their social contexts and their sexual and reproductive health, with a particular focus on youth's understandings of gender, sexuality, and the body as sites of possibility and power. A community-based sample of N = 24 youth of color was recruited from the South and West Sides of Chicago to participate in 3-day workshops. In addition to story circles and body mapping, data were collected via brief surveys with N = 24 youth, debriefing groups (n = 10 youth), and focus groups (n = 14 youth). Study data consisted of (1) body map visuals, that is, legends, mini-, and full-body maps; (2) written body map narratives; and (3) audio recordings of the story circles, body mapping activities, debriefing groups, and focus groups. All audio recordings were transcribed, deidentified, and uploaded in Dedoose for qualitative thematic analysis. Data analysis was conducted by a team of independent coders. Across all sources of data, three major themes were identified: (1) strong feelings of unsafety related to how young people's bodies are gendered, sexualized, and racialized in different social settings; (2) the extent to which adults and institutions foster youth safety; and (3) sources of young people's coping and resilience. Implications for public health research, practice, and policy are discussed.